Nested interactions between chemosynthetic lucinid bivalves and seagrass promote ecosystem functioning in contaminated sediments - Cardini, Ulisse; Marín-Guirao, Lazaro; Montilla, Luis M.; Marzocchi, Ugo; Chiavarini, Salvatore; Rimauro, Juri; Quero, Grazia Marina; Petersen, Jillian M.; Procaccini, Gabriele (Frontiers in Plant Science, 2022)
In seagrass sediments, lucinid bivalves and their chemoautotrophic bacterial symbionts consume H2S, relying indirectly on the plant productivity for the presence of the reduced chemical. Additionally, the role of lucinid bivalves in N provisioning to the plant (through N2 fixation by the symbionts) was hypothesized. Thus, lucinids may contribute to sediment detoxification and plant fitness. Seagrasses are subject to ever-increasing human pressure in coastal environments. Here, disentangling nested interactions between chemosynthetic lucinid bivalves and seagrass exposed to pollution may help to understand seagrass ecosystem dynamics and to develop successful seagrass restoration programs that consider the roles of animal-microbe symbioses. We evaluated the capacity of lucinid bivalves (Loripes orbiculatus) to promote nutrient cycling and seagrass (Cymodocea nodosa) growth during a 6-week mesocosm experiment. A fully crossed design was used to test for the effect of sediment contamination (metals, nutrients, and hydrocarbons) on plant and bivalve (alone or interacting) fitness, assessed by mortality, growth, and photosynthetic efficiency, and for the effect of their nested interaction on sediment biogeochemistry. Plants performed better in the contaminated sediment, where a larger pool of dissolved nitrogen combined with the presence of other trace elements allowed for an improved photosynthetic efficiency. In fact, pore water nitrogen accumulated during the experiment in the controls, while it was consumed in the contaminated sediment. This trend was accentuated when lucinids were present. Concurrently, the interaction between clams and plants benefitted both organisms and promoted plant growth irrespective of the sediment type. In particular, the interaction with lucinid clams resulted in higher aboveground biomass of C. nodosa in terms of leaf growth, leaf surface, and leaf biomass. Our results consolidate the notion that nested interactions involving animal-microbe associations promote ecosystem functioning, and potentially help designing unconventional seagrass restoration strategies that exploit chemosynthetic symbioses.